Kecerdasan Emosional dalam Perspektif Daniel Goleman (Analisis Buku Emotional Intelligence) - Nasution, Fauziah Mahnizar; Nasution, Hasnah; Harahap, Aprilinda M. (AHKAM, 2023)
Emotional Intelligence is a person’s ability to identify, understand and regulate the emotions of themselves and others. Emotional Intelligence must be trained and studied from an early age in order to obtain emotional intelligence because emotional intelligence does not come suddenly. This emotional Intelligence book offers several theories on how to be successful in emotional intelligence. The methodology used is descriptive qualitative research using primary and secondary data and using content analysis. The aim of this research is to improve emotional intelligence very well and explain what emotional intelligence is according to Daniel Goleman in his book Emotional Intelligence. Having emotional intelligence enables a person to recognize their own feelings and those of others as well as the ability to motivate themselves and the ability to manage emotions well in themselves and in relationships with others.